The Relationship of The Level of Knowledge, Motivation and Compliance of Nurses To the Implementation of Occupational Health and Safety Mega Buana Palopo Hospitalte - Rismayanti Yamin; Dian Furqani Hamdan; Suwandi N; Nur Asphina R. Djavo; Muh Iqra Hasan (International Journal of Health and Medicine, 2024)
Implementation is a process of putting something into practice which is influenced by internal and external factors. Implementation of occupational health and safety in hospitals concerns the nursing workforce, work methods/methods, work tools, work processes and the work environment which includes improvement, prevention, treatment and recovery. The aim of this research is to determine the relationship between knowledge, motivation and compliance of nursing staff with the implementation of occupational safety and health at Mega Buana Palopo Hospital in 2023. The method uses a quantitative type of research using analytical observational methods, using a cross sectional approach. The sample in this study amounted to 76 respondents. The sampling technique uses random sampling with research instruments, questionnaires and observations. Data analysis used the Fisher exact test and chi-square test. Factors related to the implementation of occupational health and safety for nurses were a good level of knowledge, namely 68 respondents (89.5%), 74 respondents (97%) were motivated and complied with implementation of occupational health and safety, namely 42 respondents (55.3%). The results of the study showed that there was a relationship between knowledge (p= 0.012), motivation (p = 0.034), and compliance of nursing staff (p= 0.016) with the implementation of hospital occupational health and safety. The level of knowledge, motivation and compliance of nursing staff is related to the implementation of occupational health and safety in hospitals